PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN DAERAH PASCA DESENTRALISASI FISKAL - Edy Imam Supeno; Ansari Ansari (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
The era of decentralization encourages economic growth, both in terms of revenue and expenditure so that it has increased compared to before the era of decentralization. However, the effect of fiscal decentralization is much greater on the expenditure side than the regional revenue side. This research method uses library research. The approach used in this study uses a qualitative approach which is often called the naturalistic research method because the research is carried out in natural conditions (natural setting). Meanwhile, data analysis is descriptive analytical, so that the research analysis is carried out qualitatively both on secondary data and primary data. The results showed that fiscal decentralization has a negative influence on economic growth, which means that the higher the fiscal decentralization, the lower the economic growth; Economic growth has a positive effect on the welfare of people in the regions, which means that the higher the economic growth, the higher the welfare of the people, and fiscal decentralization has a positive effect on people's welfare in growing the economy, which means that the higher the fiscal decentralization, the higher the welfare of the people. Fiscal decentralization, which has a positive effect on people's welfare, has sufficiently explained that fiscal decentralization in Indonesia on the right track.